Artificial Intelligence Network Embedding, Entrepreneurial Intention, and Behavior Analysis for College Students’ Rural Tourism Entrepreneurship - Kang, Zhonghui (Frontiers in Psychology, 2022)
To promote the development of rural economy and improve the level of entrepreneurship education in colleges and universities, the willingness and behavior of college students' rural tourism entrepreneurship are studied. Primarily, based on the previous research results, the influencing factor model is determined for college students’ entrepreneurial intention. Afterwards, a questionnaire survey is set released to collect data from a university in Xi’an. Finally, the artificial neural network (ANN) improved by genetic algorithm (GA) based on artificial intelligence network is used to study the relationship between college students' entrepreneurial intention and behavior. The simulation is carried out on MATLAB2013b software. The results show that the average evaluation accuracy is 81.13% of 60 groups of data of the unmodified back propagation neural network (BPNN) algorithm, while the average evaluation accuracy is 92.17% of the BPNN algorithm improved and optimized by GA, with an ascent of 11.04%. The BPNN algorithm improved and optimized by GA is obviously better than the unmodified BPNN algorithm. Meanwhile, the BPNN algorithm improved and optimized by GA is feasible and effective in the analysis of influencing factors of college students’ entrepreneurial intention and behavior. The research provides a basis for colleges and universities to carry out entrepreneurship education on a large scale and cultivate innovative talents.